PERAN TINGKAT PENDIDIKAN DAN SEMANGAT KERJA TERHADAP PRESTASI KERJA KARYAWAN AIOLA FOOD CARAVAN SURABAYA DENGAN KEMAMPUAN KERJA SEBAGAI VARIABEL MEDIASI - Rosalia Fantika Dalima; Subijanto; Woro Utari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The results showed that 1.) Education level had a significant negative effect on employee performance with the original sample value of -0.302. 2.) Education level has a significant positive effect on work ability with the original sample value of 0.406. 3.) Work enthusiasm has a significant positive effect on employee performance with the original sample value of 0.703. 4.) Work enthusiasm has a significant positive effect on work ability with the original sample value of 0.498. 5.) Work ability has a significant positive effect on employee performance with the original sample value of 0.517. 6.) Education level has a significant positive effect on employee performance mediated by work ability with an original sample value of 0.257. 7.) Work morale has no significant positive effect on employee performance mediated by work ability with an original sample value of 0.210.